2020
DOI: 10.3389/fcell.2020.558432
|View full text |Cite
|
Sign up to set email alerts
|

Wwox Deficiency Causes Downregulation of Prosurvival ERK Signaling and Abnormal Homeostatic Responses in Mouse Skin

Abstract: Deficiency of tumor suppressor WW domain-containing oxidoreductase (WWOX) in humans and animals leads to growth retardation and premature death during postnatal developmental stages. Skin integrity is essential for organism survival due to its protection against dehydration and hypothermia. Our previous report demonstrated that human epidermal suprabasal cells express WWOX protein, and the expression is gradually increased toward the superficial differentiated cells prior to cornification. Here, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Compared to wild type MEF cells, knockout MEF cells have a significantly increased rate of proliferation 37 . Similar observations are also shown in skin keratinocytes 56 . TGF-β upregulates F-actin bundles in cytoplasm in a WWOX-dependent manner, suggesting that WWOX is needed for the F-actin bundle formation 57 .…”
Section: Discussionsupporting
confidence: 86%
“…Compared to wild type MEF cells, knockout MEF cells have a significantly increased rate of proliferation 37 . Similar observations are also shown in skin keratinocytes 56 . TGF-β upregulates F-actin bundles in cytoplasm in a WWOX-dependent manner, suggesting that WWOX is needed for the F-actin bundle formation 57 .…”
Section: Discussionsupporting
confidence: 86%
“…Skin integrity is crucial for the survival of organisms as it acts as a barrier against various environmental factors. One study showed that WWOX protein is expressed in human epidermal suprabasal cells, and its expression progressively intensifies as the cells undergo differentiation towards the superficial layers [ 47 ]. WWOX is also involved in various biological processes, including bubbling apoptosis, transcription, RNA processing, and genomic stability, suggesting that WWOX plays a critical role in normal cellular/physiological homeostasis maintenance [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human dermal fibroblasts were purchased from Lonza (Basel, Switzerland). Lentivirus-mediated gene knockdown was performed as described previously [ 41 ] using the sequences listed in Supplementary Table 1. 5-Azacytidine (5-Aza) was obtained from MedChemExpress (#HY-10586; Monmouth Junction, NJ, USA).…”
Section: Methodsmentioning
confidence: 99%